Expert System Diagnose Disease in Poultry Using Certainty Factor Method - Oktavio Nansia; Bosker Sinaga (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
In this study, the authors conducted research to apply the Certainty Factor Method to Diagnose Diseases in Livestock and build applications in the application of Reviews These methods. Information technology is now a staple in developing a field. Along with the development of the times, proper information management is needed, so we need an Appropriate computational method. In this case the expert system method is one way to find out or identify diseases in poultry that have been infected with bacteria or viruses. A form of management information system specifically created to support a plan in making decisions to solve a case or problem. Artificial Intelligence (Artifical Intelligence) is one part of computer science that makes machines (computers) can do work as and as well as humans do. Expert System is one of the Artificial Intelligence techniques that attempts to adopt human knowledge into computers, so that computers can solve problems as is usually done by experts. Diagnosing disease in poultry is currently a problem that is still underestimated for most people, this is due to lack of knowledge or lack of information in terms of Overcoming and Preventing Contaminated, viruses or bacteria. Certainty Theory Theory was suggested by Shortlife and Buchanan in 1975 to a accommodate the uncertainty of thinking or inexact reasoning of an expert. Phrases like "maybe", "most likely", "almost Certain". To a accommodate this, Researchers conducted a certainty factor method to describe the level of expert confidence in problems in diseases Suffered by chickens already infected with dangerous viruses.